Belarus in the period of the Northern War according to the travelogue of Daniel Krman - Moyšová, Stanislava (Journal of the Belarusian State University. History, 2025)
The travelogue (itinerarium) of the Protestant priest Daniel Krman is not only a unique testimony about the Northern War, about the advance and defeat of the Swedish troops at Poltava, but it is also a precious well of sociological, ethnographic, and political knowledge relating to present-day Belarus, Ukraine, Lithuania, and Poland, i. e. to the regions he passed through as an envoy of the Upper Hungarian (Slovak speaking) Protestant estates. As an astute observer, Daniel Krman took notes on everything that crossed the coordinates of his Central European origins. The aim of this article is to map the images of the Belarus that relate to the population, religion, toponymy, architecture, and specifics of the Belarusian region in the early 18th century.
Keywords: Northern War; Belarus; 18th century; Rzeczpospolita; travelogue